Effects of Lactoferrin on Sleep Conditions in Children Aged 12–32 Months: A Preliminary, Randomized, Double-Blind, Placebo-Controlled Trial - Miyakawa M (Dove Medical Press, 2020)
Momoko Miyakawa,1 Shutaro Kubo,1 Hirotsugu Oda,1 Noriko Motoki,2 Masaru Mizuki,2 Teruomi Tsukahara,2 Miyuki Tanaka,1 Koji Yamauchi,1 Fumiaki Abe,1 Tetsuo Nomiyama2 1Food Ingredients and Technology Institute, R&D Division, Morinaga Milk Industry Co., Ltd, Zama, Kanagawa, Japan; 2Department of Preventive Medicine and Public Health, Shinshu University School of Medicine, Matsumoto, Nagano, JapanCorrespondence: Momoko MiyakawaFood Ingredients and Technology Institute, R&D Division, Morinaga Milk Industry Co., Ltd., 1-83, 5-Chome, Higashihara, Zama-City, Kanagawa-Pref. 252-8583, JapanTel +81 46252 3045Fax +81 46252 3017Email mo-miyakawa@morinagamilk.co.jpPurpose: To investigate preliminarily the effect of lactoferrin (LF)-fortified formula on sleep conditions in children.Study Design: A preliminary, randomized, double-blind, placebo-controlled trial.Methods: Healthy children between the ages of 12 and 32 months who attended nursery schools in Japan were divided into two groups and assigned a placebo or LF (48 mg/day)-fortified formula. Children’s sleep conditions were investigated before and after the 13-week intervention using the Japanese Sleep Questionnaire for Preschoolers (JSQ-P).Results: Altogether, 109 participants were randomized. Eight participants were eliminated due to lost to follow-up, withdrawal of consent, and ineligibility, with 101 participants (placebo, n = 48; LF, n = 53) included in the full analysis set (FAS) and used for analysis. Wake-up time, bedtime, and nighttime sleep were comparable between the two groups before and after intervention. The change in total JSQ-P T scores tended to improve in the LF group (placebo vs LF: 0.5 ± 6.5 vs − 1.9 ± 6.1, p = 0.074), in particular, morning symptoms significantly improved (grumpy in the morning, hard to wake-up, and hard to get out of bed) (placebo vs LF: 0.8 ± 6.2 vs − 1.9 ± 6.2, p = 0.028). A better trend was also observed in the LF group regarding restless legs syndrome (RLS)-motor (rubs feet at night and touches feet at night) (placebo vs LF: 2.3 ± 10.7 vs − 0.6 ± 13.5, p = 0.083) and insufficient sleep (stays up more than one hour later the day before a holiday and wakes up more than one hour later on a holiday) (placebo vs LF: 0.1 ± 9.8 vs − 1.7 ± 8.8, p = 0.095). No adverse drug reactions were found.Conclusion: LF intake may improve sleep condition, especially morning symptoms in children above one year of age.Keywords: lactoferrin, sleep, growing-up formula, children